Molecular Detection and Differentiation of Theileria lestoquardi, T. ovis and T. annulata in Blood of Goats and Ticks in Kermanshah Province, Iran - Mozhgan Rahmani-Varmale; Mousa Tavassoli; Bijan Esmaeilnejad (Tehran University of Medical Sciences, 2019)
Background: This study was carried out to identify Theileria spp. infections in goats and ticksin Kermanshah Province, western Iran from May-Sep 2015. Methods: For differentiation of different Theileria spp. both blood and tick samples were examined by nested PCR-RFLP. Results: Light microscopy of blood smears revealed Theileria spp. infection in 22 (5.5%), while 68 (17%) of blood samples were positive using nested PCR. Out of 68 positive samples, 85.3% (58/68) and 11.7% (8/68) were respectively positive for Theileria ovis and T. lestoquardi. Mixed infection was detected in 3% (2/68) cases. Overall, 420 ixodid ticks belong to seven different hard ticks species were collected from goats. Rhipicephalus turanicus 112 (26.7%), R. sanguineus 95 (22.6%), R. bursa, 91(21.7%), Hyalomma anatolicum, 55(13.1%), H. excavatum 27(6.4%), H. marginatum, 22(5.3%) and Dermacentor marginatus, 18(4.2%) were the main tick species infesting goats. The PCR products obtained from ticks were subjected to the differentiation of Theileria species. Respectively, 2 and 8 pools of H. marginatum and R. turanicus salivary glands were infected with T. ovis and T. lestoquardi. In addition, T. annulata and T. lestoquardi infection weredetected in three pools of H. anatolicum. Conclusion: This is the first report of goats and collected ticks to Theileria spp infection in Iran. The results suggest that T. ovis has a higher prevalence than T. lestoquardi. It is also postulated H. marginatum, R. turanicus and H. anatolicum might play an important role in the field as a vector of Theileria spp in this area.